Narratives of everyday resistance from the margins - Canham, Hugo; Langa, Malose (PINS-Psychology in Society, 2017)
In this introduction and framing to this special issue on “Narratives of everyday resistance from the margins”, we make the case that narrative method and practice can contribute to a radical scholarship of psychosocial praxis. Critical scholarship is after all the mainstay of the PINS (Psychology in society) tradition since its inception in 1983 (Anonymous, 2014). To continue with this tradition of this critical theorisation, we reflect on themes contained in the five papers that constitute this issue and beyond, especially in relation to how these themes also link with similar global issues. We argue for conceiving of the collection of stories as agential narratives which contribute to a decolonial scholarship by centring lives positioned on the margins of post-apartheid South Africa. The stories told here recognise that the capitalist, racist and patriarchal orders which create abjection and poverty reside alongside lives permeated by joy and the search for meaning. The hallmark of the stories is a narrative of resistance and the refusal to accept inequality and injustice. We posit that the narrative frame is humanising and enables scholars to centre the everyday as a site for illuminating “wretched making” and the different ways of saying no.